2006
DOI: 10.1097/00006231-200603000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of verapamil on the restoration of myocardial perfusion and functional recovery in patients with angiographic no-reflow after primary percutaneous coronary intervention

Abstract: Intracoronary verapamil restored myocardial perfusion in patients with angiographic no-reflow after PCI and lead to better functional recovery after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The P‐glycoprotein multidrug resistance 1 (MDR1) transports PS to the outer leaflet of the plasma membrane bilayer [25], and P‐glycoprotein‐deficient mice are protected against post‐IRI in the kidney [26]. The reported efficacy of verapamil in attenuating the no‐reflow phenomenon following coronary thrombosis in humans [8,10] is also consistent with the role of PS externalization in reperfusion injury. Increased intracellular calcium levels promote PS externalization [11], and verapamil is a calcium entry blocker.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The P‐glycoprotein multidrug resistance 1 (MDR1) transports PS to the outer leaflet of the plasma membrane bilayer [25], and P‐glycoprotein‐deficient mice are protected against post‐IRI in the kidney [26]. The reported efficacy of verapamil in attenuating the no‐reflow phenomenon following coronary thrombosis in humans [8,10] is also consistent with the role of PS externalization in reperfusion injury. Increased intracellular calcium levels promote PS externalization [11], and verapamil is a calcium entry blocker.…”
Section: Discussionmentioning
confidence: 89%
“…Various pharmaceutical treatments, including adenosine, nicorandil, nitroprusside, verapamil, clopidogrel, and IIb/IIIa in-hibitors, have been administered at the time of PCI in an attempt to decrease the extent of the microvascular perfusion defect [2][3][4][5][6][7][8][9][10]. However, apart from the use of clopidogrel and IIb/IIIa inhibitors, these agents are not routinely used in clinical practice to reduce no-reflow.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been implicated in liver ischemia-reperfusion injury, including reactive oxygen species generation, lipid peroxidation, alterations in calcium homeostasis, mitochondrial dysfunction, activation of Kupffer cells, and cytokine production [15][16][17]. However, mechanisms that coordinate and integrate this pathologic response are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary nicardipine is given at a median dose of 400 μg. 23 To date, multiple small studies have demonstrated the benefit of verapamil and diltiazem in treating no-reflow [24][25][26][27] . Further, a meta-analysis showed improved outcomes in individuals who received intracoronary verapamil or diltiazem.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%